1999
DOI: 10.1046/j.1365-2346.1999.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative fasting and administration of regular medications in adult patients presenting for elective surgery. Has the new evidence changed practice?

Abstract: Several studies have demonstrated that pre-operative fasting may be as short as 2 h for clear fluids and 6 h for solids with no adverse effect on volume or pH of gastric contents. Other studies suggest that many patients do not receive pre-operative prescribed medications. One hundred and fifty-three adults presenting for elective surgery (mean age 51 years) were studied to assess fasting practice. Fasting times far in excess of the recommended safe minimum were found. Mean length of fast for solids was 15 h 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
12

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
3
13
1
12
Order By: Relevance
“…Recent surgical evidence suggests that prolonged fasting (greater than two hours for fluids) is not necessary and omission of medications (especially cardiac medications) may be detrimental to outcome. 5 Perhaps a new concept of 'clear fluids and oral medications' should be introduced for those who do not need to be strictly nil by mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent surgical evidence suggests that prolonged fasting (greater than two hours for fluids) is not necessary and omission of medications (especially cardiac medications) may be detrimental to outcome. 5 Perhaps a new concept of 'clear fluids and oral medications' should be introduced for those who do not need to be strictly nil by mouth.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to the time necessary for the combined anesthetic technique. Studies have demonstrated that prolonged fasting results in greater residual gastric volume with more acid pH, while ingestion of clear fluids up to two hours before the procedure decreases the residual volume and increases the pH [12][13][14] . Besides, prolonged preoperative fasting is not only uncomfortable and unnecessary, but it can also be harmful by potentiating or perpetuating the organic response to trauma 1,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, prolonged preoperative fasting is not only uncomfortable and unnecessary, but it can also be harmful by potentiating or perpetuating the organic response to trauma 1,12 . Currently, anesthesia societies recommend more liberal rules regarding preoperative fasting, allowing the ingestion of clear liquids up to two hours before surgery 10,12 . Among patients at risk for pulmonary aspiration of gastric contents, those with gastroesophageal reflux deserve additional care 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Na comparação entre os dois períodos, observou-se no período pós-intervenção uma diminuição de 2,5 horas no tempo de jejum pré-operatório (14 horas vs. 10 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] horas; p=0,0002). Considerando apenas operações porte II, houve queda de 1,5 horas no tempo de jejum pré-operatório (12 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] horas vs 13 [5][6][7][8][9][10][11][12][13][14]…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified